Individualiosios psichologijos požiūris į pyktį, agresiją ir neapykantą – sąvokas, besikeičiančias dėl kūdikių tyrimų ir prieraišumo teorijos poveikio - Lang, Hans-Jürgen (Psichologija, 2009)
In this paper, I would like to describe how the clinical understanding of phenomena like anger, hate and aggression can be enriched by concepts derived from infant research and attachment theory. In doing so, I will draw on my own individual psychological and psychoanalytical point of view. In modern individual psychology, as it is understood in Germany, there are certainly psychoanalysts who tend to favour not just Adler’s theories, but also those of Melanie Klein or Wilfried Bion above all, just as there are those who favour the self-psychological approach (and, of course, there are other theories as well). Therefore, it goes without saying that I do not claim to represent the definitive perspective of individual psychology in my work: in individual psychology, as in psychoanalysis, there are, after all, different opinions, theories and preferences which sometimes may be predominant in specific countries. I believe that we essentially gain overall from this pluralism of theories, in spite of the dangers that may be associated with it (such as confusion of language, diffusion of the identity of school-specific concepts, undifferentiated pragmatism, etc.). Openness is, in my opinion, a very important characteristic of individual psychological theory. On the other hand, pluralism of theories does not, after all, exclude the focal points of scientific interest and the understanding of clinical phenomena, and I would like to concentrate on some of these focal points in this paper.